2000
DOI: 10.1097/00002820-200012000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Uncertainty in Illness, Stress Appraisal, and Hope on Coping in Survivors of Breast Cancer

Abstract: On the basis of Mishel's uncertainty in illness theory, Lazarus and Folkman's stress on appraisal and coping, and Herth's perspective of hope, this cross-sectional, correlational study was designed to examine the influence of uncertainty, stress appraisal, and hope on coping in 71 survivors of breast cancer. Uncertainty was measured by the Mishel Uncertainty in Illness: Community Scale, stress appraisal by the Stress Appraisal Index, hope by the Herth Hope Index, and coping by the Ways of Coping Questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 30 publications
3
87
1
Order By: Relevance
“…In previous research studying persons with serious illness (Chen, 2003 ;Her th, 1992 ;Hirano et al, 2006 ;Lin et al, 2003;Wonghongkul, 2000), physical and psychological discomfort or suffering resulting from illness has been found to negatively influence HHI scores.…”
Section: Hhi Scores and Related Factorsmentioning
confidence: 95%
See 3 more Smart Citations
“…In previous research studying persons with serious illness (Chen, 2003 ;Her th, 1992 ;Hirano et al, 2006 ;Lin et al, 2003;Wonghongkul, 2000), physical and psychological discomfort or suffering resulting from illness has been found to negatively influence HHI scores.…”
Section: Hhi Scores and Related Factorsmentioning
confidence: 95%
“…Previous research involving patients with severe dis ease has shown that lower levels of HHI are correlated with illness-related experiences and distress (Chen, 2003 ;Herth, 1992 ;Hirano et al, 2006;Lin et al, 2003 ;Wonghongkul, 2000). This is likely because severe illnesses create suffering that may persist intermittently up until the time of the HHI survey itself.…”
Section: Hhi Scores and Related Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Uncertainty, conceptualized by Mishel (1988, p. 225) as the "inability to determine the meaning of illness-related events," has been found to be a significant predictor of threat and harm appraisals in long-term breast cancer survivors (Wonghongkul, Moore, Musil, Schneider, & Deimling, 2000). No studies were identified that explored the precise relationship between uncertainty and cognitive appraisal during the post-radiation treatment transition.…”
Section: Factors Influencing Cognitive Appraisalmentioning
confidence: 99%